Antimicrobial consumption and impact of antimicrobial stewardship programmes in long-term care facilities. (May 2019) - Falcone, M.; Paul, M.; Yahav, D.; Orlando, G.; Tiseo, G.; Prendki, V.; Güerri-Fernández, R.; Gavazzi, G.; Mutters, N.T.; Cookson, B.; Tinelli Marco, M.; ,
Abstract: Background: Antimicrobials are among the most frequently prescribed drugs in long-term care facilities (LTCFs). Implementation of antimicrobial stewardship programmes (ASPs) is often challenging because of scarce data in this setting. Objectives: This narrative review aimed to provide data about antibiotic consumption in LTCFs and the need, implementation, and organization of ASPs in this setting. Source: PubMed was searched for studies assessing antimicrobial consumption and implementation of ASPs in LTCFs. The search was restricted to articles published in English in the last 10 years. Experts belonging to the ESCMID Study Group for Infections in the Elderly (ESGIE) reviewed the selected studies and evaluated the studies on ASPs according to the GRADE approach. Moreover, the quality of reporting has been assessed according to TREND and CONSORT checklists for quasi-experimental and cluster randomized clinical trials (cRCT), respectively. Content: Data on antibiotic consumption in LTCFs show great variability in LTCFs across and within countries. Reasons for this variability are difficult to analyse because of the differences in the types of LTCFs, their organization, and the population cared-for in the different LTCFs. However, studies show that the use of antibiotics among elderly patients in LTCFs, especially in cases of asymptomatic bacteriuria and influenza-like syndromes, is often inappropriate. High-quality cRCTs and low to moderate quality quasi-experimental studies show that educational interventions direct at nurse and physicians are effective in reducing unnecessary antibiotic prescriptions. Implications: There is an urgent need for ASPs tailored for LTCFs. Multifaceted organized educational interventions, involving both clinicians and nursing staff, should be advocated and require institutional intervention by health authorities. Future studies assessing the impact of well-defined ASPs in LTCFs should produce compelling evidence in this setting.